Riboflavin transporter 3 involvement in infantile Brown-Vialetto-Van Laere disease: two novel mutations. Issue 2 (14th December 2012) - Ciccolella, Marianna; Corti, Stefania; Catteruccia, Michela; Petrini, Stefania; Tozzi, Giulia; Rizza, Teresa; Carrozzo, Rosalba; Nizzardo, Monica; Bordoni, Andreina; Ronchi, Dario; D'Amico, Adele; Rizzo, Cristiano; et al.
Abstract : Background: Brown-Vialetto-Van Laere (BVVL) syndrome is a rare disorder characterised by progressive pontobulbar palsy and sensorineural deafness. Causative mutations in genes encoding human riboflavin transporter 2 (hRFT2) and 3 (hRFT3) have been identified in BVVL patients. Methods and results: We report the clinical and molecular features of a severe BVVL patient in whom screening of SLC52A3/hRFT2 was negative. Sequence analysis identified two novel compound heterozygous mutations in SLC52A2/hRFT3, namely c.155C>T and c.1255G>A, leading to the amino acid changes p.S52F and p.G419S, respectively. Functional studies show that these defects impair the gene expression of the corresponding transporter, resulting in a significant reduction of riboflavin transport. Conclusions: These findings support the pathogenetic role of SLC52A2/hRFT3 in BVVL with important clinical and therapeutic implications.